PLU1 Promotes the Proliferation and Migration of Glioma Cells and Regulates Metabolism - Wentao Dong MSc; Lude Wang MSc; Yi Pan MSc; Qi Tu MSc; Ting He MSc; Tian Zhou MSc; Jianlie Yuan MD; Minfeng Tong MD (Technology in Cancer Research & Treatment, 2023)
Objectives PLU1 is upregulated in many cancers, including breast, mammary, colorectal, and hepatocellular carcinoma. However, little is known about the potential metabolic mechanisms of PLU1 in glioma progression. Therefore, we investigated the relationship between PLU1 and glioma development. Methods We analyzed the relationship between PLU1 expression and World Health Organization (WHO) grade using clinical databases and verified the role of PLU1 in glioma development using transcriptome sequencing, Western blotting, Cell Counting Kit 8, colony formation, and wound healing assays. The relationship between PLU1 and glioma glucose metabolism was also initially explored by changing the concentration of glucose in the culture medium and was validated by metabolomics and energy metabolism. Result PLU1 expression was closely related to WHO grade and was significantly elevated in tumor tissues compared to nontumor tissues. Knockdown or inhibition of PLU1 inhibits proliferation and migration of glioma cells. In addition, we found that PLU1 expression was closely associated with glioma metabolism by transcriptomic, metabolomic, and energy-related molecular analyses and correlated with glucose metabolism. We also found that glucose concentration affects PLU1 expression, and that PLU1 expression affects intracellular glucose levels. Conclusion PLU1 is a novel regulator of metabolic reprograming and a novel strategy for the treatment of glioma.